Three-dimensional numerical simulation study of pre-cracked shale based on CT technology - Yang, Yuhan; Wu, Zhonghu; Zuo, Yujun; Song, Huailei; Wang, Wentao; Tang, Motian; Cui, Hengtao (Frontiers in Earth Science, 2023)
Due to the heterogeneity and opacity of rock media, it is difficult to truly reflect its internal three-dimensional microstructure in physical tests or numerical simulation. In this study, CT scanning technology and numerical image processing technology are used, and the finite element software RFPA-3D is used to establish a three-dimensional non-uniform numerical model that can reflect the meso structure of rock mass.In order to study the fracture mechanism of shale with prefabricated fractures, seven groups of three-dimensional numerical models with prefabricated fractures from different angles were constructed, and Brazilian fracturing numerical simulation tests were carried out. The results show that method of reconstructing 3D numerical models by CT scanning is feasible and provides a viable method for in-depth study of the micromechanics of shale. Prefabricated fractures and quartz minerals have significant effects on the tensile strength of shale, and both will weaken the destructive strength of shale specimens. The damage modes of Brazilian disc specimens containing prefabricated fissures can be divided into four categories. The damage process is divided into budding, plateauing and surge periods by acoustic emission. The crack initiation angle of the prefabricated fissure tip increases with increasing fissure angle, and the MTS criterion can be used as a basis for judging prefabricated fissure initiation. The results of the study are important guidance for the fracture initiation mechanism and fracture expansion law of the fractured layer containing natural fractures in the hydraulic fracturing process.